Malay women: religiosity, philanthropy and non-violence - Moten, Abdul Rashid (Bangladesh Institute of Islamic Thought (BIIT), 2016)
Islam is a religion of justice and peace and regards men and women as equally obliged with regard to acts of worship and interactions with others. The Qur’an addresses the believers using the expression, “believing men and women”. There is no gender bias, precedence, or prejudice in the essential language of the Qur’an. Prophet Muhammad (SAW) confirmed that women have souls in exactly the same way as men and will enter paradise if they do good. This study examines the role played by women in history, discusses the policies adopted by the government of Malaysia vis-a-vis and analyses the role played by two Muslim women, among others, in socio-economic and political arena. Based upon documentary sources and unstructured interviews, this study found that the government of Malaysia has adopted many policies to up-lift the status of women and that women have been playing an active role in Malaysia locally and globally. The two women, highlighted in this study, are highly religious, taking part in philanthropic activities, and actively promoting non-violence and peace at home and abroad.